Photocatalytic Degradation of Methyl Orange over Metalloporphyrins Supported on TiO2 Degussa P25 - Xing-Jiao Huang; Hong-Bing Ji; Xian-Tai Zhou (Molecules, 2012)
The photocatalytic activity of meso-tetraphenylporphyrins with different metal centers (Fe, Co, Mn and Cu) adsorbed on TiO2 (Degussa P25) surface has been investigated by carrying out the photodegradation of methyl orange (MO) under visible and ultraviolet light irradiation. The photocatalysts were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), diffuse reflectance UV (DRS-UV-vis) and infrared spectra. Copper porphyrin-sensitized TiO2 photocatalyst (CuP-TiO2) showed excellent activity for the photodegradation of MO whether under visible or ultraviolet light irradiation. Natural Bond Orbital (NBO) charges analysis showed that methyl orange ion is adsorbed easier by CuP-TiO2 catalyst due to the increase of induced interactions.